PENGARUH PEMBERIAN KREDIT TERHADAP TINGKAT PENDAPATAN USAHA KECIL DAN MENENGAH (UKM) (STUDI KASUS PADA PT. BANK MANDIRI (PERSERO) Tbk.) - Rosalina Febrica Mayasari (Fakultas Ekonomi Universitas Tridinanti Palembang, 2014)
The objective of this research is to know the role of the PeopleÃ¢â‚¬â„¢s Business Credit for development of UKM in Palembang (Case Study of Bank Mandiri). The role is measured from income earned UKM enterpreneurs after getting help from PeopleÃ¢â‚¬â„¢s Business Credit of Bank Mandiri. The results showed that a significant capital for revenue growth of UKM in Palembang. Thus Ha is accepted, it means capital significant or significant impact on earnings UKM entrepreneurs at 95% confidence level. Ã‚Â Key words: Capital, Loan and Micro, Small and Medium Enterprises (UKM)